Age and Alzheimer's pathology disrupt default mode network functioning via alterations in white matter microstructure but not hyperintensities. (July 2018) - Brown, Christopher A.; Jiang, Yang; Smith, Charles D.; Gold, Brian T.
Abstract: The default mode network (DMN) comprises defined brain regions contributing to internally-directed thought processes. Reductions in task-induced deactivation in the DMN have been associated with increasing age and poorer executive task performance, but factors underlying these functional changes remain unclear. We investigated contributions of white matter (WM) microstructure, WM hyperintensities (WMH) and Alzheimer's pathology to age-related alterations in DMN function. Thirty-five cognitively normal older adults and 29 younger adults underwent working memory task fMRI and diffusion tensor imaging. In the older adults, we measured cerebrospinal fluid tau and Aβ42 (markers of AD pathology), and WMH on FLAIR imaging (marker of cerebrovascular disease). We identified a set of regions showing DMN deactivation and a set of inter-connecting WM tracts (DMN-WM) common to both age groups. There were negative associations between DMN deactivation and task performance in older adults, consistent with previous studies. Decreased DMN deactivation was associated with AD pathology and WM microstructure but not with WMH volume. Mediation analyses showed that WM microstructure mediated declines in DMN deactivation associated with both aging and AD pathology. Together these results suggest that AD pathology may exert a "second-hit" on WM microstructure, over-and-above the effects of age, both contributing to diminished DMN deactivation in older adults.